The SAGE handbook of survey methodology - Wolf, Christof 1963-; Joye, Dominique; Smith, Tom W. 1949-; Fu, Yang-chih (SAGE reference, 2016)
"Survey methodology is becoming a more structured field of research, deserving of more and more academic attention. The SAGE Handbook of Survey Methodology explores both the increasingly scientific endeavour of surveys and their growing complexity, as different data collection modes and information sources are combined."-- Sage Publishing website